Coherence and connection between the good pond culture practice and the environment conscious management - Szűcs, István; Váradi, László; Békefi, Emese (Acta Agraria Debreceniensis, 2007)
According to the data indicating the decline and restructuring during the past decade, as well as the trend in the European Union member states, it can be expected that the role of traditional agriculture and fish production in direct rural employment decrease further. This also values those strategic directions for restructuring that will lead fishculture from quantity driven to quality production along with sustainable development (i.e. environmental conscious production) and multifunctional farming. This way the economic and social tensions caused by the concentration of the production and labour output can be mitigated. It is laid in the 1257/1999 Act on rural Development that farmers that enrol the agri-environmental scheme should follow the “Good Agricultural Practice” on the whole managed area. In case of agri-environmental schemes this is a precondition for which no grants are given. The adaptation of “Good Agricultural Practice” in fishproduction,where it is called: “Good Pond Culture Practice” is considered important on the basis of the above mentioned. This programme is undertaken in co-operation with the Research Institute for Aquaculture, Fisheries and Irrigation, University of Debrecen, Faculty of Agricultural Economics and Rural Development and the Association of Hungarian Fish Farmers and Product Council. The European Commission proposed the formulation of the European Fisheries and Aquaculture Fund (EFAF) for the period 2007-20013, which will replace the Financial Instruments for Fisheries Guidance (FIFG), but it also consists of several new elements and will be working differently, too. According to the proposal the budget for the Fund will be nearly 5 billion EUR (4963 million EUR). The development level of aquaculture and fisheries and the social and economic significance in the given member state will be considered when distributing the Fund between the Member States. According to the plan the Fund is organised along five priority axes, of which the most important for the Hungarian fisheries sector is No. II: Aquaculture and the processing and marketing of aquaculture and fisheries products. The main measure areas are the followings: 1. investment support for aquaculture; 2. support for aquatic-environmental schemes; 3. environmental- and animal health issues; 4. investments in processing and marketing In case of accessing support under measure area No. 2 farms are obliged to meet the requirements of the scheme beyond the “good management practice” for 5 years, which is to be supervised by the approved body of the Member State. For this reason our work is considered to be substantial. Approval of the application of “Good Pond Culture Practice” is based on two elements: first the prevailing environmental and nature conservation regulations, as well as the list of controllable conditions in the new agri-environmental agreements are to be met. “Good Pond Culture Practice” are to be conducted on the whole farm area. Its main elements are: - nutrition management, - feeding, - pond maintenance, - stocking, - harvesting, - animal welfare (storage and over-wintering).